Being a married, migrant, Nahuatl indigenous woman without paid work: a reality of a shelter for agricultural labourers in Colima, Mexico - Molina-Rodríguez, Nancy Elizabeth (Prospectiva. Revista de Trabajo Social e Intervención Social, 2020)
This work presents fragments of Maricarmen's life, with the aim of identifying the identity processes of being a migrant, Nahuatl woman, her expectations and daily life, the paid and unpaid work she does in the context of her stay in a shelter for migrant agricultural day laborers (swallow and pendular), where they live in conditions of gender and class inequality, which has among other consequences the vulnerability of their human rights, such as access to health, housing and decent work. Qualitative methodology was used and the analysis of the data was done from a gender and intersectional perspective. The results show the construction of the identity of an indigenous, migrant woman, as well as the modification of sexist and racist stereotypes interconnected with race, the Nahuatl language, age, social class and the relationship with symbolic violence.